Soybean Yield along the Texas Gulf Coast during Periods of Variable Rainfall as Influenced by Soybean Cultivar and Planting Date - W. J. Grichar; S. Biles; J. D. Janak; P. McGuill (International Journal of Agronomy)
Soybeans (Glycine max) can be planted along the upper Texas Gulf Coast from mid-March through May to take advantage of early season rains and to complete harvest before hurricane season and fall rains become a problem. When average to above average rainfall was received in May through July, yields were greater with the early April to mid-April planting; however, under high rainfall conditions throughout the season, the mid-April to early May planting produced the highest yields, with yields of over 4000 kg/ha. When rainfall was below normal, late March to early April plantings produced the greatest yields. When rainfall was above average, soybeans took longer to reach harvestability regardless of cultivar or plant dates, while under drought conditions the interval between planting and harvest was reduced. However, when planting was delayed, there was a greater risk of detrimental late-season effects from southern green stink bug (Nezara viridula) or the brown stink bug (Euschistus heros).